Controlling Investment Decisions: Hurdle Rates and Intertemporal Cost Allocation - Sunil Dutta; Stefan Reichelstein (Center for Economic Studies and ifo Institute (CESifo), 2000)
We examine alternative performance measures for a manager who has superior information about the profitability of an investment project and who contributes to periodic operating cash flows through his efforts. We find that residual income based on a suitably chosen depreciation schedule is an optimal performance measure. To address the underlying asymmetric information problem, the capital charge rate in the calculation of residual income should be equal to the firm's hurdle rate, which is the critical internal rate of return below which the principal would not want to fund the project. This hurdle rate includes the compensation cost for the better informed manager and therefore exceeds the principal's cost of capital. We also show that residual income remains an optimal performance measure in settings where multiple divisions compete for scarce investment funds. In order to solve the resource allocation problem, the capital charge rate must then be increased to a competitive hurdle rate.
Keywords: 330